2017
DOI: 10.1159/000453611
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intrapartum Fever in Term Gestations and Associated Maternal and Neonatal Sequelae

Abstract: Aim: To determine factors associated with intrapartum fever and to examine associated maternal and neonatal outcomes. Methods: Retrospective study of patients between 360/7 and 420/7 gestational weeks who entered spontaneous or induced active labor and developed temperature ≥38°C; a similar group that did not develop fever were controls. Univariate and multivariate analyses were performed with p < 0.05 as significant. Results: Fifty-four febrile patients and 306 nonfebrile controls met in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 37 publications
3
40
3
Order By: Relevance
“…A few studies have observed that women receiving epidural analgesia were at increased risk for intrapartum fever . Women with maternal pyrexia are more likely to receive antibiotics and undergo instrumental delivery and maternal pyrexia may also be associated with adverse neonatal outcomes including low Apgar scores, respiratory distress, hypotonia and neonatal seizures . However, another study suggested that epidural fever may be a benign rise in temperature not associated with neonatal neurological consequences .…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have observed that women receiving epidural analgesia were at increased risk for intrapartum fever . Women with maternal pyrexia are more likely to receive antibiotics and undergo instrumental delivery and maternal pyrexia may also be associated with adverse neonatal outcomes including low Apgar scores, respiratory distress, hypotonia and neonatal seizures . However, another study suggested that epidural fever may be a benign rise in temperature not associated with neonatal neurological consequences .…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Curtin et al, histological chorioamnionitis (OR = 3.18; 95% CI, 2.04–4.95) as well as epidural analgesia (OR = 3.40; 95% CI, 1.70–6.81) were independently associated with intrapartum fever at term 2 . Meanwhile, in a retrospective study by Burgess et al ( n = 360), there were associations between intrapartum fever above 38.0°C and longer duration of labor (OR 3.59; 95% CI, 1.97–6.55), and longer duration of ROM (OR = 4.51; 95% CI, 2.24–9.09) 22 . Our finding that a severe stage of acute chorioamnionitis and funisitis, longer duration of ROM, and a higher postpartum WBC count associated with the degree of intrapartum fever favors this maternal‐fetal inflammation hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…Also, our research results showed that the rst stage of labor was longer and the number of vaginal examinations was higher in women who received induction than those who did not (Table 2). Burgess et al [25] proved that the duration of the rst stage of labor and the number of vaginal examinations were signi cantly associated with increased risk of maternal fever. This association was probably caused by an increased risk of chorioamnionitis, and a long duration of the rst stage of labor may sustain an in ammatory process that may result in the temperature elevation in those patients.…”
Section: Discussionmentioning
confidence: 99%